2000
DOI: 10.1159/000020990
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Monitoring of Fetal pH, pO<sub>2</sub> and pCO<sub>2</sub> Using a Fiberoptic Multiparameter Sensor in Animal Models Reproducing in utero Conditions

Abstract: Objectives: To evaluate the feasibility and accuracy of continuous fetal monitoring with a multiparameter intravascular sensor (MPIS) in animal models mimicking the fetal metabolic status. Methods: First, the accuracy of the MPIS in hypoxic conditions was tested in adult rabbits (n = 6). The carotid artery (n = 4) or vein (n = 2) was catheterized with a 20-gauge cannula, housing a 500-μm Neotrend® fiberoptic sensor for pCO2, pO2, pH and temperature. Fiberoptic readings were com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…The authors concluded that extensive modi®cation of the sensor design would be necessary before the sensor could be used routinely in this area. 17 There are several clinical evaluation studies from the operating theatre and the intensive care unit. Most studies in the operating room are in adults undergoing one lung ventilation for major thoracic surgery (thoracoscopic surgery, lung transplantation), 47 83 85 or major thoracoabdominal surgery (oesophagectomy).…”
Section: Site Of Measurementmentioning
confidence: 99%
“…The authors concluded that extensive modi®cation of the sensor design would be necessary before the sensor could be used routinely in this area. 17 There are several clinical evaluation studies from the operating theatre and the intensive care unit. Most studies in the operating room are in adults undergoing one lung ventilation for major thoracic surgery (thoracoscopic surgery, lung transplantation), 47 83 85 or major thoracoabdominal surgery (oesophagectomy).…”
Section: Site Of Measurementmentioning
confidence: 99%
“…Different hypoxia-acidosis induction protocols in rabbits have been described, including either metabolic [24,25] or respiratory [11,26,27] induction protocols. Following previous literature, hypoxia-acidosis was successfully achieved combining a reduction of the fraction of inspired oxygen [14,27], breaths per minute [24] and also the inhalatory flux.…”
Section: Ventilatory Hypoxia Induction Protocol: Acid-based Metabolitmentioning
confidence: 99%
“…Although different sensors have been already tested in vivo to detect hypoxia and acidosis [11,20,22], most of them are invasive or not compatible to be inserted for long periods of time in fetal tissue without compromising fetal wellbeing.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has demonstrated the usefulness of oxygen and pH sensors to monitor acid-base status continuously in different tissues. Oxygen sensors based on either pulse-oximetry or fiber-optic sensing inserted in fetal tissue during labor in humans or placed endovascularly during endoscopic fetal surgery in sheep have shown promising results in detecting oxygen variations [5][6][7][8]. Similarly, sensors able to monitor the levels of fetal pH have also been described [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%